Inovasi Program Dakwah Di Yatim Mandiri Sumatera Utara Dalam Pemberdayaan Anak Yatim Dan Dhuafa - Harahap, Raju Panawan; Sahputra, Dika (Universitas Cokroaminoto Yogyakarta, 2026)
This study aims to qualitatively analyze the innovation of Islamic propagation (dakwah) that the North Sumatra Yatim Mandiri Institution empowers orphans and the poor through sustainable strategic programs. Based on data from in-depth interviews, direct observation, and documentation, as well as triangulation, the Yatim Mandiri Islamic propagation program is developed through five main pillars, namely education, economy, health, Islamic propagation, and humanity. Real innovation is seen in the establishment of the Insan Cendekia Mandiri Boarding School (ICMBS), the transformation of the Mandiri Entrepreneur Center (MEC), and the development of the Learning Center that integrates religious education, academics, and life skills. All of these have proven effective in increasing self-confidence, discipline, enthusiasm for learning, and independence of foster children. Islamic propagation innovation based on role models, intensive interaction, and creative coaching is a transformative, adaptive and relevant model for sustainable empowerment in various regions of Indonesia.